Drivers of Green Trust and Green Citizenship Behavior in Promoting Biofuel Adoption: Evidence from E10 Bio-gasoline in Vietnam - Son, Trinh Hoang; Phuc, Vu Truc; Minh, Ho Ngoc (International Journal of Energy Economics and Policy, 2026)
The transition toward low-carbon energy systems has positioned biofuels as an important short- to medium-term solution for reducing greenhouse gas emissions in the transportation sector, particularly in emerging economies. In Vietnam, the forthcoming mandatory adoption of E10 bio-gasoline raises concerns regarding consumer acceptance due to past challenges in earlier biofuel programs. This study investigates the psychological mechanisms through which functional attributes of E10 influence consumers’ adoption intentions. Drawing on the Stimulus–Organism–Response (S-O-R) framework, Social Exchange Theory, and the Theory of Planned Behavior, this study examines the effects of price value, perceived product quality, and facilitating conditions on green trust and green citizenship behavior, and their subsequent impact on intention to use E10 bio-gasoline. A cross-sectional survey using convenience sampling was conducted with 482 consumers in Ho Chi Minh City, Vietnam. The proposed model was analyzed using partial least squares structural equation modeling (PLS-SEM). The results reveal that price value, perceived product quality, and facilitating conditions significantly enhance green trust and green citizenship behavior. In turn, both green trust and green citizenship behavior exert strong positive effects on consumers’ intention to use E10, acting as critical mediating mechanisms. This study extends the biofuel adoption literature by emphasizing the role of trust-based and civic-oriented mechanisms in promoting sustainable energy consumption under a mandatory policy context, and offers practical implications for policymakers and energy providers in emerging economies.